Analysis of Student Errors in Solving Mathematics Problems in the Form of Descriptions in Quadratic Equation Material for High School Students Class X - Andhika Valentino Lukas; Jorry Ferry Monoarfa; Murni Sulistyaningsih (CV. ULIL ALBAB CORP, 2024)
This article discusses the analysis of students errors in solving mathematical essay questions on quadratic equations for 10th-grade high school students. The subjects of this research were 10 students from class XB at SMA Negeri 2 Tondano. The analysis of students errors based on Newman’s procedure. This type of research is a qualitative descriptive study. The instruments used in this research were written tests consisting of 5 questions and interviews with 4 representative students. The results of this study showed that there were errors in understanding the problem by 44%, errors in transformation by 42%, errors in process skil by 48%, and errors in writing finel answers by 14%.